Upaya Peningkatan Pengetahuan tentang Skoliosis melalui Pendidikan Kesehatan pada Siswa di SMK Bintara Rancaekek - Muhammad Deri Ramadhan; M. Iqbal Sutisna; Rani Puspita; Ade Lulu; Intan Jesica; Kurniawati Kurniawati; Grace Angeliqch; Listanty Widya; Irmawati Irmawati; Astriani Hapsari; Kartika Firdasari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Scoliosis is a musculoskeletal disorder characterized by an abnormal curvature of the spine with a Cobb angle of ≥10°, and most often occurs in adolescents aged 10–18 years. Initial observations at SMK Bintara Rancaekek showed a low level of knowledge among eleventh-grade students regarding scoliosis, including signs and symptoms, risk factors, and prevention efforts. This study aimed to determine the effectiveness of health education in improving students' knowledge about scoliosis through a quasi-experimental one-group pretest–posttest design. Education was provided using presentation media, educational videos, leaflets, and a demonstration of the Adam's Forward Bend Test. The pretest results showed that students' knowledge was still low in various aspects, such as understanding the early signs of scoliosis (34.2%), risk factors (52.6%), and the function of physical examinations (15.8%). After being provided with education, there was a significant increase in knowledge in all indicators. Eighty percent of students were able to identify the type of idiopathic scoliosis, 72% understood the risk factors, 88% knew the Cobb angle criteria, and 92% understood the impact of severe scoliosis on the respiratory system. The improvement in posttest scores indicates that health education effectively increased students' understanding and awareness of scoliosis. Health education has been shown to be an important strategy in supporting the early detection and prevention of scoliosis in adolescents, thereby encouraging healthier postural behaviors in the school environment.